Lithium ion secondary battery, charging method thereof and electric device

By mixing lithium-containing transition metal oxides and lithium-containing transition metal phosphates into the positive electrode active material of lithium-ion secondary batteries, and adding cyclic sulfate compounds to the electrolyte, the problem of poor storage performance of lithium-ion secondary batteries is solved, and high power density and good storage performance are achieved.

CN119833717AInactive Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510003877.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

While improving power performance, existing lithium-ion secondary batteries have poor storage performance, affecting the storage and service life of the battery.

Method used

The positive electrode active material includes lithium-containing transition metal oxides and lithium-containing transition metal phosphates, and cyclic sulfate compounds are added to the electrolyte solution to improve the side reaction between the positive electrode active material and the electrolyte solution and inhibit the dissolution of the transition metal.

Benefits of technology

While maintaining high power density, it significantly improves the storage performance of lithium-ion secondary batteries and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833717A_ABST
    Figure CN119833717A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a lithium ion secondary battery, a charging method thereof and a power utilization device. The lithium ion secondary battery comprises a positive pole piece and an electrolyte, the positive pole piece comprises a positive active material, the positive active material comprises a first positive active material and a second positive active material, the first positive active material comprises a lithium-containing transition metal oxide, and the second positive active material comprises a lithium-containing transition metal phosphate; the electrolyte comprises a solvent, an additive and a lithium salt, wherein the additive comprises a cyclic sulfate compound. The lithium ion secondary battery has good power density and high-temperature storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and more specifically, to a lithium-ion secondary battery and a charging method and an electrical device thereof. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, and have thus achieved great development.

[0003] Mixing lithium-containing transition metal oxides and lithium-containing transition metal phosphates can improve the power performance of lithium-ion secondary batteries, but the storage performance deteriorates. Storage performance has an important impact on the preservation, transportation and service life of lithium-ion secondary batteries. Therefore, how to improve the storage performance of lithium-ion secondary batteries is a technical problem that needs to be solved urgently. Summary of the invention

[0004] The present application is made in view of the above-mentioned technical problems, and its purpose is to provide a lithium-ion secondary battery and a charging method and an electrical device thereof, wherein the lithium-ion secondary battery takes into account both power performance and storage performance.

[0005] In a first aspect, a lithium-ion secondary battery is provided, comprising a positive electrode plate and an electrolyte, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode film layer arranged on at least one side of the positive electrode current collector; the positive electrode film layer comprises a positive electrode active material, and the positive electrode active material comprises a first positive electrode active material and a second positive electrode active material, wherein the first positive electrode active material comprises a lithium-containing transition metal oxide, and the second positive electrode active material comprises a lithium-containing transition metal phosphate; the electrolyte comprises a solvent, an additive and a lithium salt, and the additive comprises a cyclic sulfate ester compound.

[0006] In an embodiment of the present application, the positive electrode active material includes both a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate, and the electrolyte includes a cyclic sulfate additive. Thus, while improving the power performance of the lithium-ion secondary battery, it is possible to improve the side reaction between the positive electrode active material and the electrolyte, inhibit the dissolution of transition metals in the positive electrode active material, and enhance the storage performance of the lithium-ion secondary battery.

[0007] In some embodiments, the charging cut-off voltage v of the lithium-ion secondary battery satisfies: 4.3V≤v≤5V.

[0008] In some embodiments, the cyclic sulfate compound includes at least one of a compound having a molecular formula (I) or a modified compound thereof: Among them, R1-R4 include at least one of halogenated or unhalogenated H, alkyl with 1-6 carbon atoms, alkenyl with 2-6 carbon atoms, alkoxy with 1-6 carbon atoms, acyloxy with 1-6 carbon atoms, ester with 2-6 carbon atoms, and cyclic sulfate with 4-7 membered rings.

[0009] In some embodiments, R1-R4 further comprises at least one of the groups of formula (II-I) to formula (II-IV): in, Indicates the bonding position, R5 includes at least one of halogen, alkyl having 1-6 carbon atoms, haloalkyl having 1-6 carbon atoms, and alkoxy having 1-6 carbon atoms, and the groups of formula (II-I) to (II-IV) are bonded to R1 and R3, or to R2 and R4.

[0010] In some embodiments, the cyclic sulfate ester compound has a polycyclic structure.

[0011] Cyclic sulfates with polycyclic structures can form denser interfacial films.

[0012] In some embodiments, the cyclic sulfate ester compound comprises at least one of the compounds of formula (II) to formula (I-XII):

[0013] In some embodiments, based on the total mass of the electrolyte, the mass fraction m1 of the cyclic sulfate ester compound satisfies: 0.1%≤m1≤5%.

[0014] In some embodiments, 0.5%≤m1≤2%.

[0015] In some embodiments, the ionic conductivity σ of the electrolyte satisfies: 7.5 mS / cm≤σ≤15 mS / cm.

[0016] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, lithium bisoxalate borate, lithium difluorooxalate borate or lithium tetrafluorooxalate phosphate; optionally, the lithium salt includes lithium hexafluorophosphate.

[0017] In some embodiments, the concentration c of the lithium salt in the electrolyte satisfies: 0.9M≤c≤1.2M.

[0018] In some embodiments, the solvent includes at least one of a carbonate solvent and a carboxylate solvent.

[0019] In some embodiments, the carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate.

[0020] In some embodiments, the carboxylate solvent includes at least one of methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl acrylate, and ethyl acrylate.

[0021] In some embodiments, based on the total mass of the electrolyte, the carbonate solvent includes ethylene carbonate, and the mass fraction m2 of the ethylene carbonate satisfies: 10%≤m2≤30%.

[0022] In some embodiments, the additive includes fluoroethylene carbonate.

[0023] In some embodiments, in a cross section of the positive electrode film layer along the thickness direction of the positive electrode sheet, primary particles of the first positive electrode active material surround at least a portion of agglomerates of primary particles of the second positive electrode active material.

[0024] In some embodiments, the BET1 of the positive electrode active material satisfies: 0.5 m 2 / g≤BET1≤4.5m 2 / g.

[0025] In some embodiments, the volume distribution particle size Dv50 of the positive electrode active material satisfies: 3.2 μm≤Dv50≤6 μm.

[0026] In some embodiments, the average particle size D1 of the primary particles of the first positive electrode active material satisfies: 1.6 μm≤D1≤2.6 μm; and / or the average particle size D2 of the primary particles of the second positive electrode active material satisfies: 40 nm≤Dv502≤250 nm.

[0027] In some embodiments, the lithium-containing transition metal oxide comprises a molecular formula of Li n1 (Ni x1 Co y1 Mn z1 ) 1- n G n O 2-m K mor at least one of the compounds or modified compounds thereof, wherein G includes one or more of Zr, Al, Nb, Sr, B, Ba, Mg, Sn, Y, Na, Si, W and Ti, K includes one or more of P, F, N, S, F, Cl and I, 0.6≤n1≤1.5, 0.3≤x1≤0.7, 0.02≤y1≤0.15, x1+y1+z1=1, 0<n≤0.1, 0<m≤0.1, 0<r≤0.1.

[0028] In some embodiments, the average mass concentration ratio of the K element in the outer region corresponding to a radius of 1 / 6 extending from the surface of the primary particle containing the lithium transition metal oxide to the center is greater than the average mass concentration ratio of the K element in the core region corresponding to a radius of 1 / 6 extending from the center of the primary particle to the surface.

[0029] In some embodiments, the average mass concentration ratio a of the K element in the outer region extending from the surface of the primary particle of the lithium-containing transition metal oxide to the center corresponding to 1 / 6 of the radius satisfies: 0.1%≤a≤0.5%.

[0030] In some embodiments, the average mass concentration ratio b of the K element in the core region extending from the center of the primary particle of the lithium-containing transition metal oxide to the surface corresponding to 1 / 6 of the radius satisfies: 0.01%≤b≤0.05%.

[0031] In some embodiments, the lithium-containing transition metal phosphate comprises a molecular formula of Li n2 Fe x2 Mn y2 P z2 O j Q q or at least one of a compound or a modified compound thereof, wherein Q includes at least one of Al, Na, K, Mg, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.6≤n2≤1.15, 0<x2, 0≤y2, 0.9≤x2+y2≤1, 0.95≤z2≤1, 3.5≤j≤4, and 0≤q≤0.1.

[0032] In some embodiments, based on the total mass of the positive electrode active material, the mass fraction m3 of the lithium-containing transition metal phosphate satisfies: 5%≤m3≤40%.

[0033] In some embodiments, when the lithium-containing transition metal phosphate includes lithium iron phosphate, 5%≤m3≤15%; or when the lithium-containing transition metal phosphate includes lithium manganese iron phosphate, 10%≤m3≤40%.

[0034] In some embodiments, the specific surface area BET2 of the positive electrode sheet satisfies: 2m 2 / g≤BET2≤5m 2 / g.

[0035] In some embodiments, the positive electrode plate has a plate porosity p measured by a true density method that satisfies: 22%≤p≤28%.

[0036] In some embodiments, the compaction density ρ of the positive electrode sheet satisfies: 3.0 g / cm 3 ≤ρ≤3.5g / cm 3 .

[0037] In a second aspect, an electrical device is provided, wherein the electrical device comprises a lithium-ion secondary battery according to any possible implementation of the first aspect.

[0038] In a third aspect, a charging method for a lithium-ion secondary battery is provided, the charging method comprising charging the lithium-ion secondary battery at a preset rate Cset to a cutoff voltage v; charging the lithium-ion secondary battery at the cutoff voltage v to a cutoff current i; wherein 4.3V≤v≤5V, 0.02C≤i≤0.1C. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0040] Figure 1 This is a cross-sectional view of a positive electrode sheet in the thickness direction.

[0041] Figure 2 This is a partial view of a cross-section of a positive electrode sheet in the thickness direction.

[0042] Figure 3 A schematic diagram of a lithium-ion secondary battery.

[0043] Figure 4 A schematic diagram of a battery cell.

[0044] Figure 5 The present invention is a schematic flow chart of a charging method for a lithium-ion secondary battery. DETAILED DESCRIPTION

[0045] Hereinafter, the embodiments of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0046] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0047] In the description of this application, it should be noted that, unless otherwise specified, "multiple" means more than two; the terms "upper", "lower", "left", "right", "inner", "outer", etc., indicating directions or positional relationships, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as limiting this application. In addition, the terms "first", "second", "third", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0048] If not otherwise specified, in this application, the phrase "A and / or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A and / or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0049] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0050] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0051] Unless otherwise specified, the following terms have the following meanings. Any undefined terms have their generally accepted meanings in the art.

[0052] If mentioned, "charge cut-off voltage" refers to the highest charging voltage reached by a lithium-ion secondary battery during the charging process. When the lithium-ion secondary battery reaches this voltage, the charging process will stop to prevent the lithium-ion secondary battery from being overcharged, damaging the lithium-ion secondary battery or causing safety problems.

[0053] If mentioned, "discharge platform voltage" refers to the voltage corresponding to the "platform area" in the voltage-capacity or voltage-time curve under constant current discharge conditions. In the voltage-capacity or voltage-time curve of the discharge process, the voltage first drops rapidly as the discharge capacity or discharge time increases, then the voltage remains almost unchanged or changes very little, and then the voltage drops rapidly to the cut-off voltage. The part of the curve where the voltage remains almost unchanged or changes very little is the "platform area". The discharge platform voltage can be the voltage corresponding to the platform area (voltage remains almost unchanged) or the median of the voltage range corresponding to the platform area (voltage changes). The discharge platform voltage of a certain material is usually measured by a half-cell consisting of the material and metallic lithium.

[0054] If mentioned, "lithium-containing transition metal phosphate" refers to a type of salt including lithium, transition metal, and phosphate ion, such as lithium iron phosphate materials, lithium iron manganese phosphate materials, etc.

[0055] As mentioned, "lithium-containing transition metal oxides" refers to a class of oxides including lithium elements and transition metal elements. Structurally, it includes ternary materials with layered structures, LiCoO2, LiNiO2, etc., and also includes LiMn2O4 with spinel structure, etc. Ternary materials refer to lithium transition metal oxides including three different transition metal elements. It should be understood that ternary materials can also be doped or coated with trace amounts of other transition metal elements, and it is generally believed that ternary materials doped or coated with other transition metal elements are still ternary materials.

[0056] As mentioned, "cyclic sulfate compounds" refer to cyclic compounds including an -O-SO2-O- group, wherein the -O-SO2-O- is generally located on the ring of the cyclic compound.

[0057] Next, embodiments of the present application are introduced.

[0058] The battery cell of a lithium-ion secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the charge and discharge process of a lithium-ion secondary battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. Among them, the electrolyte plays a role in conducting active ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which prevents the positive and negative electrodes from short-circuiting while allowing active ions to pass through, so that the electrochemical reaction proceeds normally.

[0059] Improving the energy density of lithium-ion secondary batteries has always been a research focus in the field of batteries. The positive electrode active material is one of the direct factors that directly affect the energy density of lithium-ion secondary batteries. Lithium-containing transition metal oxides have a high gram capacity, which helps to improve the energy density of lithium-ion secondary batteries. However, the power performance of lithium-containing transition metal oxides at low SOC is poor. Specifically, in the late stage of discharge of a lithium-ion secondary battery whose positive electrode includes a lithium-containing transition metal oxide, at low SOC (for example, 10% SOC and below), the voltage of the lithium-ion secondary battery has a sudden drop process, resulting in poor power performance of the lithium-ion secondary battery at low SOC, affecting the overall power density of the lithium-ion secondary battery. When the lithium-ion secondary battery is at a low SOC, the lithium-containing transition metal phosphate has a discharge platform to adjust the power performance of the lithium-ion secondary battery at a low SOC. Therefore, a lithium-ion secondary battery with both energy density and power density can be obtained by compounding lithium-containing transition metal phosphates and lithium-containing transition metal oxides in the positive electrode active material.

[0060] However, the applicant has found that, although the principle is not yet clear, when the positive electrode active material includes a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate, the lithium-containing transition metal oxide actually accelerates oxygen release, and reacts with the electrolyte to cause the transition metal in the positive electrode active material to dissolve and deposit at the negative electrode, resulting in poor storage performance of the lithium-ion secondary battery.

[0061] In view of this, an embodiment of the present application provides a lithium-ion secondary battery and a charging method and an electrical device thereof. The positive electrode active material of the lithium-ion secondary battery includes a lithium-containing transition metal oxide and a second positive electrode active material, and the electrolyte includes a cyclic sulfate ester compound, which can enable the lithium-ion secondary battery to have good storage performance while having a high power density.

[0062] Next, the lithium-ion secondary battery provided by the present application is introduced.

[0063] [Lithium-ion secondary battery]

[0064] First, a lithium-ion secondary battery is provided, comprising a positive electrode plate and an electrolyte. The positive electrode plate comprises a positive electrode current collector and a positive electrode film layer disposed on the surface of at least one side of the positive electrode current collector. The positive electrode film layer comprises a positive electrode active material, and the positive electrode active material comprises a first positive electrode active material and a second positive electrode active material. Among them, the first positive electrode active material comprises a lithium-containing transition metal oxide, and the second positive electrode active material comprises a lithium-containing transition metal phosphate. The electrolyte comprises a solvent, an additive and a lithium salt, and the additive comprises a cyclic sulfate ester compound.

[0065] The positive electrode active materials include lithium-containing transition metal oxides and lithium-containing transition metal phosphates, which make the lithium-ion secondary battery have a good power density, and also make the lithium-containing transition metal oxides more likely to release oxygen and react with the electrolyte. The possible reason is that the particles of lithium-containing transition metal oxides are relatively large and the particles of lithium-containing transition metal phosphates are usually small. The grading of the two increases the specific surface area of ​​the entire positive electrode active material and the surface area of ​​the positive electrode sheet. The contact area between the positive electrode active material and the electrolyte is larger, which aggravates the side reactions with the electrolyte. On the one hand, the side reactions between the electrolyte and the positive electrode active material may cause the transition metal in the positive electrode active material to dissolve, destroy the interface film between the positive electrode active material and the electrolyte, and further aggravate the occurrence of side reactions. On the other hand, after the transition metal is dissolved, it may also be deposited on the negative electrode, blocking the transmission of lithium ions and affecting the electrochemical reaction of lithium ions. As a result, the storage performance and service life of the lithium-ion secondary battery are affected.

[0066] The lithium-ion secondary battery of the present application introduces a cyclic sulfate compound as an additive in the electrolyte. The cyclic sulfate compound can undergo ring opening in the electrolyte and participate in the film-forming reaction of the positive and negative electrodes. The cyclic sulfate compound participates in the interfacial film-forming reaction to form a dense and uniform interfacial film. Its participation in film formation at the positive electrode can effectively reduce the contact area between the positive electrode active material and the electrolyte and inhibit the dissolution of transition metals; its participation in film formation at the negative electrode can prevent the dissolved metal ions from depositing at the negative electrode. Therefore, in the case where the positive electrode active material includes a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate, by using a cyclic sulfate compound as an additive in the electrolyte, the storage performance of the lithium-ion secondary battery can be effectively improved, so that the lithium-ion secondary battery has good power density and storage performance.

[0067] For positive electrode active materials, the specific surface area refers to the total area of ​​the material per unit mass. In other words, the specific surface area of ​​the positive electrode active material is the ratio of the sum of the specific surface areas of all particles of the positive electrode active material to the mass of all particles.

[0068] After the lithium-containing transition metal oxide is mixed with the lithium-containing transition metal phosphate, the specific surface area of ​​the positive electrode active material increases. The possible reasons are: on the one hand, the lithium-containing transition metal phosphate itself has small particles, and its specific surface area is larger than that of the lithium-containing transition metal oxide with larger particles. After mixing with the lithium-containing transition metal oxide, the specific surface area of ​​the positive electrode active material can be increased; on the other hand, in the process of preparing the positive electrode active material, the lithium-containing transition metal oxide and the lithium-containing transition metal phosphate are usually physically mixed by ball milling or the like. During the physical mixing process, the particles of the two materials may be further broken, so that the number of small particles in the positive electrode active material increases, and the specific surface area of ​​the positive electrode active material is further increased. It should be understood that the larger particles and smaller particles described in this application refer to the larger particle size of the particles and the smaller particle size of the particles.

[0069] In some embodiments, the charging cut-off voltage v of the lithium-ion secondary battery satisfies: 4.3V≤v≤5V.

[0070] Specifically, v can be 4.3V, 4.35V, 4.4V, 4.45V, 4.5V, 4.55V, 4.6V, 4.65V, 4.7V, 4.75V, 4.8V, 4.85V, 4.9V, 4.95V, 5V, or its value is within the range obtained by combining any two of the above values.

[0071] Lithium-containing transition metal oxides have a high gram capacity, which helps to improve the energy density of lithium-ion secondary batteries. However, during the actual charging process of lithium-ion secondary batteries, not all lithium ions in lithium-containing transition metal oxides can be released from the material. Under the same mass or volume, the higher the charging cut-off voltage of the lithium-ion secondary battery, the more lithium ions can be released from the positive electrode active material, thereby increasing the gram capacity of the positive electrode active material, making the lithium-ion secondary battery have a higher energy density.

[0072] At the same time, for lithium-containing transition metal oxides, the lithium-containing transition metal is more likely to release oxygen at a higher charge cut-off voltage, and the structure of the lithium-containing transition metal phosphate may become unstable.

[0073] In the embodiment of the present application, thanks to the cyclic sulfate compounds in the electrolyte, a stable interface film can be formed between the solid-liquid interface to reduce the side reactions of the lithium-containing transition metal oxide at a high charging cut-off voltage, and the interface film also enables the lithium-containing transition metal phosphate to maintain a stable structure at a high charging cut-off voltage. As a result, the lithium-ion secondary battery of the present application can achieve a charging cut-off voltage of 4.3V-5V, further improving the energy density of the lithium-ion secondary battery.

[0074] It should be understood that, taking into account the normal error of the test conditions, the charging cut-off voltage charged under the above conditions within the range of 25℃±2℃, if it falls within the range specified in this application, can be equivalent to the test result at 25℃ and is deemed to fall within the scope of this application.

[0075] The discharge platform voltage of the active material is related to the type of material, the lattice structure of the material and its lithium storage mechanism. During the cycle of the lithium-ion secondary battery, the discharge platform voltage of the active material will change with the change of the active material. The charging cut-off voltage of the lithium-ion secondary battery can be set within the above range according to factors such as the voltage window of the electrolyte, the potential difference between the positive and negative electrodes, and the discharge platform voltage of the active material. Among them, the voltage window of the electrolyte refers to a voltage range that allows the electrolyte to maintain a constant state without decomposition. The components of the electrolyte will affect the voltage window of the electrolyte. The potential difference between the positive and negative electrodes is related to the type of active material.

[0076] In some embodiments, the cyclic sulfate ester compound includes at least one of the compounds of formula (I) or modified compounds thereof: Among them, R1-R4 include at least one of halogenated or unhalogenated H, alkyl with 1-6 carbon atoms, alkenyl with 2-6 carbon atoms, alkoxy with 1-6 carbon atoms, acyloxy with 1-6 carbon atoms, ester with 2-6 carbon atoms, and cyclic sulfate with 4-7 membered rings.

[0077] In some embodiments, R1-R4 further comprises at least one of the groups of formula (II-I) to formula (II-IV): in, Indicates the bonding position, R5 includes at least one of halogen, alkyl having 1-6 carbon atoms, haloalkyl having 1-6 carbon atoms, and alkoxy having 1-6 carbon atoms, and the groups of formula (II-I) to (II-IV) are bonded to R1 and R3, or to R2 and R4.

[0078] In some embodiments, the cyclic sulfate ester compound has a polycyclic structure. In other words, the cyclic sulfate ester compound has two or more polycyclic rings. For example, the cyclic sulfate ester compound has two or more five-membered rings.

[0079] Compared with cyclic sulfate compounds with one polycyclic ring, cyclic sulfate compounds with a polycyclic structure can form a more complete and dense interface film, which can more effectively inhibit the dissolution of transition metals and prevent the dissolved metal ions from depositing at the negative electrode, thereby further improving the storage performance of lithium-ion secondary batteries and enabling lithium-ion secondary batteries to have good power density and storage performance.

[0080] In some embodiments, the cyclic sulfate ester compound comprises at least one of the compounds of formula (II) to formula (I-XII):

[0081] Cyclic sulfates can be decomposed in the electrolyte to form sulfur-containing polymers, which helps to improve the integrity and density of the interfacial film, thereby reducing side reactions at the solid-liquid interface.

[0082] In some embodiments, based on the total mass of the electrolyte, the mass fraction m1 of the cyclic sulfate ester compound satisfies: 0.1%≤m1≤5%; optionally, 0.5%≤m1≤2%.

[0083] Specifically, m1 can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2 .7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, or its value is within the range obtained by combining any two of the above values. The more the content of cyclic sulfate ester compounds in the electrolyte, the more conducive it is to the formation of the interface film. If the content of cyclic sulfate ester compounds is too much, the generated interface film may be too thick, which is not conducive to the release of lithium ions from the active material, and may deteriorate the internal impedance of the lithium ion secondary battery and affect the service life of the lithium ion secondary battery. Therefore, by controlling the mass fraction of cyclic sulfate ester compounds in the electrolyte within a specific range, it can help improve the service life of the lithium ion secondary battery while improving the storage performance of the lithium ion secondary battery.

[0084] In some embodiments, the ionic conductivity σ of the electrolyte satisfies: 7.5 mS / cm≤σ≤15 mS / cm.

[0085] Specifically, σ can be 7.5mS / cm, 8mS / cm, 8.5mS / cm, 9mS / cm, 9.5mS / cm, 10mS / cm, 10.5mS / cm, 11mS / cm, 11.5mS / cm, 12mS / cm, 12.5mS / cm, 13mS / cm, 13.5mS / cm, 14mS / cm, 14.5mS / cm, 15mS / cm, or its value is within the range obtained by combining any two of the above values. The higher the ionic conductivity of the electrolyte, the more conducive it is to the lithium ion dynamics inside the lithium ion secondary battery, so that lithium ions can be quickly transmitted in the electrolyte, and the lithium ion secondary battery can achieve a larger charge rate or discharge rate, further improving the power density of the lithium ion secondary battery. Too high ionic conductivity of the electrolyte is not conducive to the stability of the electrolyte, and may cause an increase in side reactions inside the lithium ion battery, affecting the storage performance of the lithium ion secondary battery. Therefore, by controlling the ionic conductivity of the electrolyte within a suitable range, it helps to improve the lithium ion kinetics during the cycle of the secondary battery in some embodiments, and helps to improve the power density and storage performance of the secondary battery in some embodiments.

[0086] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, lithium bisoxalate borate, lithium difluorooxalate borate or lithium tetrafluorooxalate phosphate; optionally, the lithium salt includes lithium hexafluorophosphate.

[0087] In the embodiment of the present application, when the charging cut-off voltage of the lithium ion secondary battery is 4.3 V-5 V, lithium hexafluorophosphate is preferably used as the lithium salt. Lithium hexafluorophosphate still has good chemical stability under high pressure and is not prone to side reactions with other components in the lithium ion secondary battery.

[0088] In some embodiments, the concentration c of the lithium salt in the electrolyte satisfies: 0.9M≤c≤1.2M.

[0089] Specifically, it can be 0.9M, 0.95M, 1M, 1.1M, 1.15M, 1.2M, or a value within the range obtained by combining any two of the above values.

[0090] The greater the concentration of lithium salt, the greater the number of lithium ions in the electrolyte, which helps to improve the ionic conductivity of the electrolyte and the lithium ion dynamics inside the lithium-ion secondary battery. For example, during the discharge process, when the lithium-ion secondary battery is in a low SOC state, the lithium ion concentration in the negative electrode active material is low, and the difficulty of lithium ion escape leads to a slow lithium ion migration rate. In the same time, lithium ions cannot escape from the negative electrode to reach the positive electrode, while the electrons moving through the external circuit have reached the positive electrode. The lithium ions in the electrolyte can first quickly reach the positive electrode and embed into the positive electrode active material, thereby increasing the lithium ion migration rate inside the lithium-ion secondary battery. For another example, if the concentration of lithium salt is too high, it may cause the viscosity of the electrolyte to increase, which is not conducive to the rapid movement of lithium ions in the electrolyte and affects the lithium ion dynamics. Therefore, by controlling the concentration of lithium salt within a specific range, the lithium ion dynamics inside the lithium-ion secondary battery can be improved, so that the lithium-ion secondary battery can also stably output electrical energy under low SOC conditions, further improving the power density of the lithium-ion secondary battery.

[0091] In some embodiments, the solvent includes at least one of a carbonate solvent and a carboxylate solvent.

[0092] In some embodiments, the carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate.

[0093] Carbonate solvents help to increase the ionic conductivity of the electrolyte, thereby helping to reduce the internal impedance of the lithium-ion secondary battery and further improving the power performance of the lithium-ion secondary battery.

[0094] In some embodiments, the carboxylate solvent includes at least one of methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl acrylate, and ethyl acrylate.

[0095] Carboxylate solvents also help to increase the ionic conductivity of the electrolyte, thereby helping to reduce the internal impedance of the secondary lithium-ion secondary battery, and further improve the power performance of the lithium-ion secondary battery.

[0096] In some embodiments, the carbonate solvent includes ethylene carbonate, and based on the total mass of the electrolyte, the mass fraction m2 of ethylene carbonate satisfies: 10%≤m2≤30%.

[0097] Specifically, m2 can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, or its value is within the range obtained by combining any two of the above values.

[0098] Ethylene carbonate has a relatively high dielectric constant, which helps to dissociate lithium salts in the electrolyte, thereby increasing the ionic conductivity of the electrolyte and further helping to improve the power performance of lithium-ion secondary batteries.

[0099] In some embodiments, the additive includes fluoroethylene carbonate.

[0100] By introducing fluoroethylene carbonate into the additive, fluoroethylene carbonate is also involved in the film-forming reaction of the interface film, which helps to increase the inorganic components in the interface film and compound with the organic components formed by cyclic sulfate substances, so that the formed interface film is more stable, further improving the storage performance of lithium-ion secondary batteries.

[0101] In some embodiments, in a cross section of the positive electrode film layer along the thickness direction of the positive electrode sheet, primary particles of the first positive electrode active material surround at least a portion of agglomerates of primary particles of the second positive electrode active material.

[0102] Figure 1 This is a cross-sectional view of a positive electrode sheet of the present application along the thickness direction. Figure 2 It is a partial cross-sectional view of a positive electrode sheet in the thickness direction.

[0103] like Figure 1-2 As shown, the primary particles of lithium-containing transition metal oxides have a larger particle size and are closer to blocks; the primary particles of lithium-containing transition metal phosphates have a smaller particle size and form agglomerates, and the shape of the agglomerates is closer to round or oval. The primary particles of lithium-containing transition metal oxides surround at least part of the primary particle agglomerates of lithium-containing transition metal phosphates, and there are few pores between the particles, which is conducive to the compaction of the positive electrode film layer.

[0104] In some embodiments, the BET1 of the positive electrode active material satisfies: 0.5 m 2 / g≤BET1≤4.5m 2 / g.

[0105] Specifically, BET1 can be 0.5m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, or its value is within the range obtained by combining any two of the above values. As mentioned above, the particles of lithium-containing transition metal oxides are usually larger, and the particles of lithium-containing transition metal phosphates are usually smaller. The combination of the two will increase the specific surface area of ​​the positive electrode active material and intensify the side reaction between the positive electrode active material and the electrolyte. Therefore, in the embodiments of the present application, when the positive electrode active material includes a lithium-containing transition metal phosphate and a lithium-containing transition metal oxide, controlling the specific surface area of ​​the positive electrode active material within a suitable range can help improve the side reaction between the positive electrode active material and the electrolyte, thereby improving the storage performance of the lithium-ion secondary battery.

[0106] The BET of the positive electrode active material can be tested by means known in the art. For example, the lithium-ion secondary battery to be tested can be disassembled to obtain the positive electrode plate, and the conductive agent, binder and other components can be removed by sintering, and the remaining components on the positive electrode current collector can be scraped for BET testing to obtain the BET of the positive electrode active material. It should be understood that some positive electrode active materials may contain a small amount of carbon, which may be removed during the sintering process, but due to the small content, it is generally believed that its effect on the BET of the positive electrode active material can be ignored.

[0107] In some embodiments, the volume distribution particle size Dv50 of the positive electrode active material satisfies: 3.2 μm≤Dv50≤6 μm.

[0108] Specifically, Dv50 can be 3.2μm, 3.4μm, 3.6μm, 3.8μm, 4μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm, 5μm, 5.2μm, 5.4μm, 5.6μm, 5.8μm, 6μm, or its value is within the range obtained by combining any two of the above values. The larger the volume particle size distribution of the positive electrode active material, the smaller its specific surface area. Therefore, by controlling the volume particle size distribution of the positive electrode active material, the specific surface area of ​​the positive electrode active material can be regulated within the above range, which helps to improve the side reaction between the positive electrode active material and the electrolyte and improve the storage performance of the lithium-ion secondary battery.

[0109] In some embodiments, the average particle size D1 of the primary particles of the first positive electrode active material satisfies: 1.6 μm≤D1≤2.6 μm; and / or the average particle size D2 of the primary particles of the second positive electrode active material satisfies: 40 nm≤D2≤250 nm.

[0110] Specifically, D1 can be 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, or its value is within the range obtained by combining any two of the above values. D2 can be 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, or its value is within the range obtained by combining any two of the above values.

[0111] The primary particles of lithium-containing transition metal phosphates are nanometer-sized, with a small average particle size, a short lithium ion transmission path, a fast transmission speed, and good kinetic performance. Including such lithium-containing transition metal phosphates in the positive electrode active material enables the lithium-ion secondary battery to have good power performance. At the same time, since the primary particles of lithium-containing transition metal phosphates have a small particle size, it also helps to increase the specific surface area of ​​the positive electrode active material, thereby increasing the contact area between the positive electrode active material and the electrolyte, affecting the storage performance of the lithium-ion secondary battery. Therefore, under the premise that the electrolyte includes cyclic sulfate compounds, by controlling the average particle size of the primary particles of lithium-containing transition metal phosphates and the average particle size of the primary particles of lithium-containing transition metal oxides within a suitable range, the BET of the positive electrode active material can be regulated after compounding, so that the Dv50 and BET of the positive electrode active material and the BET of the positive electrode sheet are within a suitable range, which can improve the power performance and storage performance of the lithium-ion secondary battery.

[0112] In some embodiments, the BET of the primary particles of the first positive electrode active material is 0.5 m 2 / g-1m 2 / g; and / or the BET of the primary particles of the second positive electrode active material is 7m 2 / g-16m 2 / g.

[0113] In some embodiments, the lithium-containing transition metal oxide includes a molecular formula of Li n1 (Ni x1 Co y1 Mn z1 ) 1-n G n O 2-m K r or at least one of the compounds or modified compounds thereof, wherein G includes one or more of Zr, Al, Nb, Sr, B, Ba, Mg, Sn, Y, Na, Si, W and Ti, K includes one or more of P, F, N, S, F, Cl and I, 0.6≤n1≤1.5, 0.3≤x1≤0.7, 0.02≤y1≤0.15, x1+y1+z1=1, 0<n≤0.1, 0<m≤0.1, 0<r≤0.1.

[0114] By selecting lithium-containing transition metal oxides with a nickel content of 0.3-0.7, it is helpful to improve the problem of lithium-nickel mixing at a higher charge cut-off voltage. By doping G and K elements, it is helpful to further stabilize the lattice of lithium-containing transition metal oxides and further improve the problem of lithium-nickel mixing at a higher charge cut-off voltage.

[0115] In some embodiments, the average mass concentration ratio of the K element in the outer region corresponding to a radius of 1 / 6 extending from the surface of the primary particle containing the lithium transition metal oxide to the center is greater than the average mass concentration ratio of the K element in the core region corresponding to a radius of 1 / 6 extending from the center of the primary particle to the surface.

[0116] The modification of K element can stabilize the lattice structure of the lithium-containing transition metal oxide, so that it can ensure the stability of the material structure under the high voltage of 4.3V-5V. In the present application, the lithium-containing transition metal oxide is modified by K element, which can be specifically manifested as doping and / or coating. In some embodiments, the modification is manifested as coating.

[0117] When the average mass concentration ratio of K element at the surface of primary particles of lithium-containing transition metal oxide is greater than the average mass concentration ratio of K element at the center of the primary particles, K element is enriched on the surface of material particles. The inert coating can alleviate the side reactions at the positive electrode interface, ensure that the material structure is not damaged under high voltage, and enable the secondary battery to have better high-temperature cycle performance and high-temperature storage performance.

[0118] In some embodiments, the average mass concentration ratio a of the K element in the outer region corresponding to 1 / 6 of the radius extending from the surface of the primary particle containing the lithium transition metal oxide toward the center satisfies: 0.1%≤a≤0.5%.

[0119] When the mass concentration of K element at the surface of the primary particles of the lithium-containing transition metal oxide is 0.1%-0.5%, the lithium-ion secondary battery of the present application has good high-temperature storage performance.

[0120] In some embodiments, the average mass concentration ratio b of the K element in the core region extending from the center of the primary particle of the lithium-containing transition metal oxide to the surface corresponding to 1 / 6 of the radius satisfies: 0.01%≤b≤0.05%.

[0121] When the mass concentration of K element at the center of the primary particle containing lithium transition metal oxide is 0.01%-0.05%, the lithium ion secondary battery of the present application has good high-temperature storage performance.

[0122] In some embodiments, the content of phosphorus at the surface of the lithium-containing transition metal oxide primary particle is greater than the content of phosphorus at the center of the primary particle.

[0123] When the phosphorus content at the surface of the primary particles of the lithium-containing transition metal oxide is greater than the phosphorus content in the center of the primary particles, a good coating layer will be formed due to the rich phosphorus at the grain boundaries, which will passivate the surface of the lithium-containing transition metal oxide material, provide a good physical barrier between the electrode and the electrolyte, reduce the side reactions between the positive electrode active material and the electrolyte, ensure that the material structure is not damaged under high voltage, and enable the secondary battery to have better high-temperature storage performance and cycle performance.

[0124] In other embodiments, examples of lithium-containing transition metal oxides may include, but are not limited to, lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc.

[0125] It should be understood that for the aforementioned positive electrode active materials, the lithium-ion secondary battery will be accompanied by the deintercalation and consumption of Li during the charge and discharge process, and the molar content of Li in the positive electrode active material is different when the lithium-ion secondary battery is discharged to different states. In the enumeration of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is applied to the battery system, and the molar content of Li will change after the charge and discharge cycle. In the enumeration of positive electrode active materials in this application, the molar content of O is only an ideal state value. The release of lattice oxygen will cause the molar content of O to change, and the actual molar content of O will fluctuate.

[0126] In some embodiments, the lithium-containing transition metal phosphate includes a molecular formula of Li n2 Fe x2 Mn y2 P z2 O j Q q or at least one of a compound or a modified compound thereof, wherein Q includes at least one of Al, Na, K, Mg, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.6≤n2≤1.15, 0<x2, 0≤y2, 0.9≤x2+y2≤1, 0.95≤z2≤1, 3.5≤j≤4, and 0≤q≤0.1.

[0127] In other embodiments, examples of lithium phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0128] In some embodiments, based on the mass of the positive electrode active material, the mass fraction m3 of the second positive electrode active material satisfies: 5%≤m3≤40%.

[0129] Specifically, m3 can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, or its value is within the range obtained by combining any two of the above values.

[0130] In some embodiments, in Li z (Ni a Co b Mn c ) d M e O f A g When c is less than 0.4, the second positive electrode active material can be selected as lithium iron phosphate. m3 can be in the range of 5%-15%, and can be selected as 10%. By mixing 5%-15% of lithium iron phosphate, the lithium ion secondary battery can have a good power density.

[0131] In some embodiments, in Li z (Ni a Co b Mn c ) d M e O f A g When c is greater than or equal to 0.4, the second positive electrode active material can be selected as lithium iron manganese phosphate. m3 can be in the range of 10%-40%, and can be selected as 30%. By mixing 10%-40% lithium iron manganese phosphate, the lithium ion secondary battery can have a good power density.

[0132] By mixing 5%-40% of lithium-containing transition metal phosphate in the positive electrode active material, the power density of the lithium-ion secondary battery is improved. At the same time, the applicant also noted that compared with mixing a small amount (e.g., less than 5%) of lithium-containing transition metal phosphate, when the positive electrode active material includes 5%-40% of lithium-containing transition metal phosphate, the specific surface area of ​​the positive electrode active material is larger, and the side reaction problem with the electrolyte is more serious. Therefore, a cyclic sulfate compound with a polycyclic structure can be preferably used as an additive. Compared with a cyclic sulfate compound with a monocyclic structure, a cyclic sulfate compound with a polycyclic structure can form a denser interface film. Thus, by using a high proportion of lithium-containing transition metal phosphate and a cyclic sulfate compound with a polycyclic structure, the power density and storage performance of the lithium-ion secondary battery can be further improved.

[0133] In some embodiments, the specific surface area BET2 of the positive electrode sheet satisfies: 2m 2 / g≤BET2≤5m 2 / g.

[0134] Specifically, BET2 can be 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, or its value is within the range obtained by combining any two of the above values. The larger the specific surface area of ​​the electrode, the improved wettability of the electrolyte, the electrolyte provides an ion conduction path for the material, improves the kinetic performance, and thus improves the power performance of the lithium-ion secondary battery. At the same time, the risk of side reactions is also greater. Therefore, the lithium-ion secondary battery of the present application can have a higher power density and good storage performance by controlling the specific surface area of ​​the positive electrode within a suitable range.

[0135] In some embodiments, the positive electrode plate has a porosity p measured by a true density method that satisfies: 22%≤p≤28%.

[0136] Specifically, p can be 22%, 23%, 24%, 25%, 26%, 27%, 28%, or its value is within the range obtained by combining any two of the above values. The higher the porosity of the electrode sheet, the improved wettability of the electrolyte, the electrolyte provides an ion conduction path for the material, improves the kinetic properties, and thus improves the power performance of the lithium-ion secondary battery. At the same time, the risk of side reactions is also greater. Therefore, the lithium-ion secondary battery of the present application can have a higher power density and good storage performance by controlling the porosity of the positive electrode sheet within a suitable range.

[0137] In some embodiments, the compaction density ρ of the positive electrode sheet satisfies: 3.0 g / cm 3 ≤ρ≤3.5g / cm 3 .

[0138] Specifically, ρ can be 3.0 g / cm 3 、3.1g / cm 3 、3.2g / cm 3 , 3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3, or its value is within the range obtained by combining any two of the above values. The greater the compaction density of the positive electrode sheet, the more conducive it is to improving the energy density of the lithium-ion secondary battery. However, if the compaction density of the positive electrode sheet is too large, it may affect the infiltration of the electrolyte into the positive electrode film layer, which can reduce the contact between the electrolyte and the positive electrode active material but seriously affect the lithium ion dynamics. Therefore, by controlling the compaction density of the positive electrode sheet within a suitable range, the lithium-ion secondary battery can have a higher energy density, power density and storage performance.

[0139] Next, taking a lithium-ion secondary battery as a specific example, the positive electrode sheet, negative electrode sheet, separator and electrolyte in the lithium-ion secondary battery are introduced in detail. It should be understood that the lithium-ion secondary battery is only used as an example, and the solution provided in this application can also be applied to other types of secondary batteries, such as sodium-ion batteries, magnesium-ion batteries, lithium-sulfur batteries, etc.

[0140] [Negative electrode]

[0141] The negative electrode sheet generally includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. The negative electrode film layer includes a negative electrode active material.

[0142] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0143] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0144] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0145] In some embodiments, the negative electrode active material is a silicon-containing material. The silicon-containing material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, silicon-containing alloys, or silicon-oxygen-carbon composite materials. By selecting a silicon-containing material as the negative electrode active material, it is beneficial to further improve the volume energy density of the battery cell 10. Combined with the structural design of the battery cell 10 in the aforementioned embodiment, the battery cell 10 can have both high energy density and excellent safety performance.

[0146] In one embodiment, the negative electrode film layer further includes a binder. The binder can be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0147] In some embodiments, the negative electrode film layer further includes a conductive agent, which can be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0148] In some embodiments, the negative electrode film layer further includes other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0149] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet are formed into a negative electrode slurry. For example, the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a negative electrode slurry. Then, the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0150] [Positive electrode]

[0151] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector. The positive electrode film layer includes a positive electrode active material. The positive electrode active material includes a first positive electrode active material and a second positive electrode active material.

[0152] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0153] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0154] In some embodiments, the positive electrode film layer further includes a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0155] In some embodiments, the positive electrode film layer further includes a conductive agent. As an example, the conductive agent may also include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, graphene, and carbon nanofibers.

[0156] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet are respectively formed into positive electrode slurry. For example, the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry. Then, the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0157] [Electrolyte]

[0158] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.

[0159] In some embodiments, the electrolyte includes a solvent, and the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0160] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0161] [Isolation film]

[0162] The present application has no particular limitation on the type of isolation membrane. For example, any known porous isolation membrane with good chemical stability and mechanical stability may be selected.

[0163] In some embodiments, the separator includes a porous substrate, and the material of the porous substrate can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The porous substrate can be a single-layer film or a multi-layer composite film, without particular limitation. When the porous substrate is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0164] In some embodiments, the isolation film further comprises a porous coating layer, which can play a role of heat resistance and / or adhesion.

[0165] In some embodiments, the porous coating layer includes heat-resistant particles. The heat-resistant particles may include at least one of inorganic particles and organic particles.

[0166] In some embodiments, the inorganic particles may include one or more of inorganic particles having a dielectric constant of 5 or more, inorganic particles having ion conductivity but not storing ions, or inorganic particles capable of electrochemical reactions.

[0167] In some embodiments, the inorganic particles having a dielectric constant of 5 or more may include boehmite, aluminum oxide, barium sulfate, magnesium oxide, magnesium hydroxide, silicon oxide, tin dioxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, hafnium dioxide, cerium oxide, zirconium titanate, barium titanate, magnesium fluoride, aluminum hydroxide, barium oxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, calcium fluoride, barium fluoride, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, Pb(Zr,Ti)O3 (abbreviated as PZT), Pb1-mLamZr1-nTinO3 (abbreviated as PLZT, 0<m<1, 0<n<1), Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (abbreviated as PMN-PT), and one or more of their respective modified inorganic particles. Optionally, the modification of each inorganic particle can be chemical modification and / or physical modification.

[0168] In some embodiments, inorganic particles having ion conductivity but not storing ions may include Li3PO4, lithium titanium phosphate, Lix1 Ti y1 (PO4)3, Lithium Aluminum Titanate Phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum titanate lithium Li x4 La y4 TiO3, Lithium Germanium Phosphate Thiophosphate x5 Ge y5 P z2 S w 、Lithium Nitride Li x6 N y6 、SiS2 glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4 One or more of 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7. This can improve the ion conductivity of the isolation membrane.

[0169] In some embodiments, the inorganic particles capable of undergoing an electrochemical reaction may include one or more of lithium-containing transition metal oxides, lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.

[0170] In some embodiments, the organic particles may include at least one of a thermoplastic resin polymer, a thermosetting resin polymer, or a cross-linked polymer.

[0171] In some embodiments, the thermoplastic resin polymer may include one or more of polycarbonate organic particles, polymethyl methacrylate organic particles, polyoxymethylene organic particles, polyamide organic particles, styrene-acrylonitrile copolymer, polyphenylene sulfide organic particles, polyetheretherketone organic particles, polyimide organic particles, polysulfone organic particles, polyethersulfone organic particles, polyphenylene sulfone organic particles, polybenzimidazole organic particles, polyamideimide organic particles, and polyethyleneimine organic particles.

[0172] In some embodiments, the thermosetting resin polymer may include one or more of phenolic resin organic particles, polymer particles containing triazine ring structural units, epoxy resin organic particles, unsaturated polyester resin organic particles, urea-formaldehyde resin organic particles, and furan resin organic particles.

[0173] In some embodiments, the cross-linked polymer may include one or more of cross-linked styrene-based organic particles and silicon-containing organic cross-linked resin particles.

[0174] In some embodiments, the porous coating layer includes binder particles. The binder particles may include homopolymers or copolymers of acrylate monomer units, homopolymers or copolymers of acrylic acid monomer units, homopolymers or copolymers of styrene monomer units, polyurethane compounds, rubber compounds, homopolymers or copolymers of fluorinated olefin monomer units, homopolymers or copolymers of olefin monomer units, homopolymers or copolymers of unsaturated nitrile monomer units, homopolymers or copolymers of alkylene oxide monomer units, and one or more of the modified compounds of the above homopolymers or copolymers.

[0175] In some embodiments, the binder particles may include copolymers of acrylic acid ester monomer units and styrene monomer units, copolymers of acrylic acid monomer units and styrene monomer units, copolymers of acrylic acid monomer units and acrylic acid ester monomer units and styrene monomer units, copolymers of styrene monomer units and unsaturated nitrile monomer units, copolymers of styrene monomer units and olefin monomer units and unsaturated nitrile monomer units, polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, polyethylene, polypropylene, polyacrylonitrile, polyethylene oxide, copolymers of different fluorine-containing olefin monomer units, copolymers of fluorine-containing olefin monomer units and vinyl monomer units, copolymers of fluorine-containing olefin monomer units and acrylic acid monomer units, copolymers of fluorine-containing olefin monomer units and acrylic acid ester monomer units, and one or more of the modified compounds of the above homopolymers or copolymers.

[0176] In some embodiments, the binder particles may include butyl acrylate-styrene copolymer, butyl methacrylate-isooctyl methacrylate copolymer, isooctyl methacrylate-styrene copolymer, methacrylate-methacrylic acid-styrene copolymer, methyl acrylate-isooctyl methacrylate-styrene copolymer, butyl acrylate-isooctyl methacrylate-styrene copolymer, butyl acrylate-isooctyl methacrylate-styrene copolymer, butyl methacrylate-isooctyl methacrylate-styrene copolymer, butyl methacrylate-isooctyl methacrylate-styrene copolymer, butyl methacrylate-isooctyl methacrylate-styrene copolymer, styrene-acrylonitrile copolymer, styrene-butadiene-acrylonitrile copolymer, methyl acrylate-styrene-acrylonitrile copolymer, isooctyl methacrylate-styrene-acrylonitrile copolymer, styrene-vinyl acetate copolymer, styrene-vinyl acetate-pyrrolidone copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-trifluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene-acrylic acid copolymer, vinylidene fluoride-hexafluoropropylene-acrylate copolymer, and one or more of the modified compounds of the above copolymers.

[0177] In some embodiments, the coating may further include a dispersant, for example, may include but is not limited to one or more of dispersants such as alkylphenol polyoxyethylene ether, polyacrylic acid dispersants, and cellulose dispersants. As an example, the dispersant may include but is not limited to one or more of sodium carboxymethyl cellulose, sodium polyacrylate, and ammonium polyacrylate.

[0178] Figure 3 It is a schematic diagram of a lithium-ion secondary battery of the present application. Figure 4 This is a schematic diagram of a battery cell of the present application. Figure 3-4 As shown, the lithium ion secondary battery 10 may include one or more battery cells 20 to meet different power requirements. In the case where the lithium ion secondary battery 10 includes only one battery cell 20 , the lithium ion secondary battery 10 is the battery cell 20 .

[0179] The lithium-ion secondary battery 10 may further include a casing, the interior of which is a hollow structure, and a plurality of battery cells 20 are contained in the casing. For example, a plurality of battery cells 20 are connected in parallel, in series, or in a mixed combination and placed in the casing. The casing may include a first casing portion 101 and a second casing portion 102, which cover each other to form the casing. The shapes of the first casing portion 101 and the second casing portion 102 may be determined according to the shapes of the components contained therein, for example, they may be determined according to the shape of the combination of the plurality of battery cells 20 contained therein, and at least one of the first casing portion 101 and the second casing portion 102 may have an opening. For example, as Figure 3As shown, only one of the first box body 101 and the second box body 102 may be a hollow cuboid with an opening, and the other may be a plate-shaped to cover the opening. Taking the second box body 102 as a hollow cuboid with an opening and the first box body 101 as a plate-shaped example, the first box body 101 covers the opening of the second box body 102 to form a box with a closed chamber, which can be used to accommodate multiple battery cells 20.

[0180] For example, unlike Figure 3 As shown, the first box body 101 and the second box body 102 can both be hollow cuboids and each have an open face, the opening of the first box body 101 and the opening of the second box body 102 are arranged opposite to each other, and the first box body 101 and the second box body 102 are buckled together to form a box with a closed chamber, which can be used to accommodate multiple battery cells 20. Multiple battery cells 20 are connected in parallel, in series, or in a mixed combination and placed in the box formed by the first box body 101 and the second box body 102 being buckled together.

[0181] In some embodiments, the lithium-ion secondary battery 10 may further include other components. For example, the lithium-ion secondary battery 10 may further include a busbar component, which may be used to achieve electrical connection between multiple battery cells 20, such as parallel connection, series connection, or mixed connection. Specifically, the busbar component may achieve electrical connection between the battery cells 20 by connecting the electrode terminals of the battery cells 20; or, the busbar component may also achieve electrical connection between the battery cells 20 by connecting other components of the battery cells 20. The busbar component may be fixed to the corresponding component of the battery cell 20 by welding, for example, it may be fixed to the electrode terminal, the sealing structure, or the housing by welding, etc., and the embodiments of the present application are not limited thereto.

[0182] The battery cells 20 may directly form the lithium-ion secondary battery 10 , or may first form a battery module, and then a plurality of battery modules may form the lithium-ion secondary battery 10 .

[0183] [Electrical devices]

[0184] The embodiment of the present application provides an electric device, comprising the lithium-ion secondary battery 10 described in the above embodiment.

[0185] The electrical device may be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, an electric tool, and the like. The vehicle may be a fuel vehicle, a gas vehicle, or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle, or an extended-range vehicle, and the like; the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, and the like; the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, and the like; the electric tool may include a metal cutting electric tool, a grinding electric tool, an assembly electric tool, and an electric tool for railways, such as an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an impact drill, a concrete vibrator, and an electric planer, and the like. The embodiments of the present application do not impose any special restrictions on the above-mentioned electrical devices.

[0186] The present application provides an electrical device, which is a vehicle.

[0187] The vehicle can be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A motor, a controller and a lithium-ion secondary battery 10 can be arranged inside the vehicle, and the controller is used to control the lithium-ion secondary battery 10 to power the motor. For example, a lithium-ion secondary battery 10 can be arranged at the bottom, front or rear of the vehicle. The lithium-ion secondary battery 10 can be used to power the vehicle. For example, the lithium-ion secondary battery 10 can be used as an operating power supply for the vehicle, for the circuit system of the vehicle, for example, for the working power demand during the start-up, navigation and operation of the vehicle. In another embodiment of the present application, the lithium-ion secondary battery 10 can not only be used as an operating power supply for the vehicle, but also as a driving power supply for the vehicle, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle.

[0188] [Charging method]

[0189] The embodiment of the present application also provides a charging method for the lithium-ion secondary battery 10 . Figure 5 This is a schematic flow chart of a charging method for a lithium-ion secondary battery 10 according to the present application.

[0190] like Figure 5 As shown, the charging method 300 includes:

[0191] S301, charging the lithium-ion secondary battery at a preset rate Cset to a cut-off voltage v.

[0192] S302, charging the lithium-ion secondary battery at a cut-off voltage v to a cut-off current i.

[0193] Among them, 4.3V≤v≤5V, 0.02C≤i≤0.1C.

[0194] It should be understood that the preset magnification Cset can be any preset value, for example, it can be 0.1C, 0.2C, 0.5C, 1C, 2C, 3C, etc.

[0195] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0196] [Examples and Comparative Examples]

[0197] Example 1

[0198] (1) Preparation of positive electrode sheet

[0199] The positive electrode active material, the binder polyvinylidene fluoride, and the conductive agent super P are mixed in a weight ratio of 97:1.5:1.5, and the solvent N-methylpyrrolidone (NMP) is added and stirred to form a positive electrode slurry; then the slurry is coated on the current collector aluminum foil, and after drying, cold pressing, striping, cutting, etc. are performed to form a positive electrode sheet of a lithium-ion battery. Among them, the positive electrode active material includes a first positive electrode active material Li (Ni 55 Co 12 Mn 33 ) 0.98 Zr 0.02 O 1.97 P 0.03 and a second positive electrode active material LiFePO4 with a mass fraction of 10%, the BET1 of the positive electrode active material is 2.1m 2 / g. BET2 of positive electrode = 2.9m 2 / g, the compaction density of the positive electrode sheet ρ = 3.25g / cm 3 .

[0200] (2) Preparation of negative electrode sheet

[0201] The negative electrode active material graphite, the conductive agent carbon black, the thickener sodium carboxymethyl cellulose (CMC-Na), and the binder styrene-butadiene rubber (SBR) are mixed in a weight ratio of 97:0.5:1:1.5, added into the solvent deionized water, stirred to form a negative electrode slurry, and the negative electrode slurry is obtained under the action of a vacuum mixer; then the slurry is coated on the current collector copper foil, and after drying, it is cold pressed, slit, cut into pieces, etc. to make the negative electrode sheet of the lithium-ion battery.

[0202] (3) Preparation of electrolyte

[0203] In an argon atmosphere glove box with a water content of <1ppm and an oxygen content of <1ppm, non-aqueous solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 3:7 to obtain a mixed solvent, additives II-I and FEC were added to the mixed solvent, and finally 1M lithium salt LiPF6 was added, and mixed and stirred until dissolved. Among them, based on the total mass of the electrolyte, the mass proportion of additive II-I is 1%, and the mass proportion of FEC is 3%. The ionic conductivity of the electrolyte is 8.5mS / cm.

[0204] (4) Isolation film

[0205] Polyethylene is used as the isolation membrane.

[0206] (5) Preparation of secondary battery monomers

[0207] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, and the electrode assembly is obtained after winding. The electrode assembly is placed in a shell, and the electrolyte is injected, and then packaged to obtain a secondary battery cell.

[0208] Examples 2-13, Comparative Examples 1-3

[0209] Compared with Example 1, the difference is that the parameters of the positive electrode active material or the electrolyte are different from those in Example 1, as shown in Table 1 for details.

[0210] Product parameters of Examples 1-13 and Comparative Examples 1-3. Table 1: Product parameters of Examples 1-13 and Comparative Examples 1-3

[0211] In Table 1, "Additive" indicates the type of additive in the electrolyte; "m1" indicates the mass fraction of cyclic sulfate compounds in the electrolyte; "m'" indicates the mass fraction of fluoroethylene carbonate in the electrolyte; "Positive Electrode Material 2" indicates the second positive electrode active material; "m3" indicates the mass fraction of the second positive electrode active material in the positive electrode active material; "Dv50" indicates the volume average particle size of the positive electrode active material; "BET1" indicates the specific surface area of ​​the positive electrode active material; "BET2" indicates the specific surface area of ​​the positive electrode sheet; "p" indicates the porosity of the positive electrode sheet; "FEC" indicates fluoroethylene carbonate.

[0212] The battery performance test was performed on Examples 1-13 and Comparative Examples 1-3 in Table 1 to obtain the battery performance data shown in Table 2.

[0213] Table 2: Battery performance of Examples 1-13 and Comparative Examples 1-3

[0214] In Table 2, “Power density” indicates the power density of the lithium ion secondary battery 30S 10% SOC; “High temperature storage capacity retention rate” represents the capacity retention rate of the secondary battery cell stored at 60° C. for 60 days.

[0215] According to the comparative analysis of the embodiments and the comparative examples, the power density and high temperature storage performance of the embodiments 1 to 13 are better than those of the comparative examples 1 to 3. It is proved that when the positive electrode active material includes a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate, and when the electrolyte includes a cyclic sulfate additive, the lithium ion secondary battery can have good power performance and high temperature storage performance at the same time.

[0216] Examples 1-4 verify that various cyclic sulfate ester additives can enable lithium-ion secondary batteries to have both good power performance and high-temperature storage performance.

[0217] According to the comparative analysis of Examples 1, 5-8, within the range of 0.1%-2%, the greater the mass fraction of the cyclic sulfate ester additive, the greater the power density of the lithium-ion secondary battery, and the better the high-temperature storage performance. Within the range of 2%-5%, the greater the mass fraction of the cyclic sulfate ester additive, the greater the power density of the lithium-ion secondary battery, and the higher the high-temperature storage performance. The possible reason is that as the mass fraction of the additive increases, the interface film thickens, affecting the internal impedance of the lithium-ion secondary battery. Therefore, by controlling the mass fraction of the cyclic sulfate ester additive within the range of 0.1%-5%, it can help improve the power performance and high-temperature storage performance of the lithium-ion secondary battery.

[0218] According to the comparative analysis of Examples 1, 9, and 11, by adjusting the mass ratio of the first positive electrode active material and the second positive electrode active material, the specific surface area and Dv50 of the positive electrode active material can be adjusted, so that the specific surface area and porosity of the positive electrode sheet are within an appropriate range.

[0219] According to the comparative analysis of Examples 1, 4, 9-10, it can be seen that the power density of Examples 1 and 4 is better than that of Examples 9-10, indicating that the higher the mass proportion of the second positive electrode active material, the more beneficial it is to the power performance of the lithium-ion secondary battery. In Examples 9-10, where the mass proportion of the second positive electrode active material is low, the additive of Formula II with a single ring structure and the additive of Formula I-VII with a polycyclic structure can effectively improve the high temperature storage performance of the lithium-ion secondary battery. In Examples 1 and 4, where the mass proportion of the second positive electrode active material is high, the improvement effect of the additive of Formula II with a single ring structure is limited, and the high temperature storage performance of Example 1 is not as good as that of Example 4. Thus, it is proved that when the mass proportion of the second positive electrode active material is high (for example, 5% and above), the combination of a cyclic sulfate compound with a polycyclic structure can further improve the power density and storage performance of the lithium-ion secondary battery.

[0220] Example 12 verifies that when the second positive electrode active material includes lithium iron manganese phosphate, the solution of the present application can also improve the power performance and high-temperature storage performance of the lithium-ion secondary battery.

[0221] From the comparative analysis of Example 1 and Example 13, it can be seen that the high-temperature storage performance of the lithium-ion secondary battery can be further improved by introducing FEC into the electrolyte.

[0222] The following is a brief introduction to the test methods of the physical and chemical parameters and performance parameters involved in the embodiments of the present application. It should be understood that the following test methods are only examples, and other test methods known in the art may also be used for testing.

[0223] 1. Test method for mass content

[0224] The content of Fe element can be determined by performing elemental analysis using inductively coupled plasma optical emission spectrometry (ICP, Ametek, model: SPECTROARCOSICP-OES) with reference to standards YS / T1006.2-2014, GB / T23367.2-2009 or YS / T1028.5-2015.

[0225] Nuclear magnetic resonance spectroscopy (NMR) can be used to detect the mass fraction of additives in the electrolyte. The specific test steps can be: add 500μL of deuterated reagent to the NMR tube in a glove box filled with nitrogen, take 100μL of non-aqueous electrolyte sample and add it to the NMR tube, shake the NMR tube to dissolve the non-aqueous electrolyte into the deuterated reagent, and use Oxford Instruments' desktop NMR spectrometer X-Pulse for testing. Since non-aqueous electrolytes are very sensitive to moisture, the NMR test and sample preparation are carried out in a nitrogen atmosphere (H2O content is less than 0.1ppm, O2 content is less than 0.1ppm), and the instruments related to the test also need to be pre-washed with pure water and dried in a vacuum environment at 60°C for more than 48 hours. The deuterated reagent is prepared according to the following steps: deuterated dimethyl sulfoxide (DMSO-d6), deuterated acetonitrile and trifluoromethylbenzene are dried with 4A molecular sieves at a temperature above 25°C for more than 3 days to ensure that the water content of all reagents is less than 3ppm. The moisture tester can be the 831KF coulometric moisture tester of Swiss Metrom Co., Ltd. Then, 10mL of dried DMSO-d6 and 300μL of dried internal standard trifluoromethylbenzene are mixed evenly in a glove box filled with nitrogen to obtain a first solution, 10mL of dried deuterated acetonitrile and 300μL of dried internal standard trifluoromethylbenzene are mixed evenly to obtain a second solution, and the first solution and the second solution are mixed evenly to obtain a deuterated reagent.

[0226] The content of solvent in the electrolyte is quantitatively analyzed by organic gas chromatography analysis method with reference to standard GB / T 9722-2006.

[0227] The content of lithium salt in the electrolyte is quantitatively analyzed by ion chromatography analysis method according to the reference standard JY / T020-1996.

[0228] 2.Dv50 test method

[0229] Referring to the standard GB / T 19077-2016, the volume average particle size Dv50 of the material can be obtained by testing the material using a laser particle size analyzer (such as Malvern Master Sizer3000).

[0230] Calculation: Calculate the particle size at the 50% position on the volume particle size distribution curve from small to large, which is Dv50.

[0231] 3.BET’s testing method

[0232] The specific surface area of ​​solid substances is determined by a specific surface and porosity analyzer with reference to the standard GB / T 19587-2017 or GB / T19587-2004 gas adsorption BET method.

[0233] Pretreatment: Use a special sample tube to take an appropriate amount of sample, heat and vacuum degas for 2 hours, and weigh the total weight after cooling to room temperature, and subtract the mass of the sample tube to obtain the sample mass.

[0234] Test: Place the sample tube into the workstation and measure the amount of gas adsorbed on the solid surface at different adsorption pressures at a constant low temperature. Based on the BET multilayer adsorption theory and its formula, the monolayer adsorption of the sample is obtained, thereby calculating the specific surface area per unit mass of the solid sample.

[0235] Adsorption gas: nitrogen, adsorption pressure points: 0.05 / 0.10 / 0.15 / 0.20 / 0.25 / 0.30, test atmosphere: high-purity liquid nitrogen atmosphere.

[0236] 4. Test method of ionic conductivity

[0237] The test method is in accordance with HG / T 4067-2015. The ionic conductivity of the electrolyte to be tested is tested with a conductivity meter: about 100 mL of the sample to be tested is taken from a dry, clean, corrosion-resistant sample bottle, and sealed in a constant temperature water bath at 25±0.5℃. When the temperature of the sample to be tested is constant, the sample bottle cap is replaced with a rubber stopper with an electrode inserted. When the temperature is within the range of 25±0.5℃, the data is read, which is the ionic conductivity of the sample to be tested.

[0238] 5. Power density test method

[0239] Normal temperature power density test method: At 25°C, charge the secondary battery to 4.5V at 1C constant current, then charge to a cut-off current of 0.05C at 4.5V constant voltage, let stand for 10 minutes, then discharge to 2.5V at 0.5C constant current, and record the discharge capacity D0 and discharge energy density W0 at this time. Then, let the battery stand for 30 minutes, charge to 4.5V at 1C constant current, then charge to a cut-off current of 0.05C at 4.5V constant voltage, let stand for 10 minutes, discharge the battery to 0.9 times D0 capacity at 0.5C constant current (10% SOC state at this time), let stand for 30 minutes, discharge at a test current for 30s until it is discharged to 2.5±0.05V, and record the terminal voltage V1 and the maximum discharge current I1.

[0240] Battery power density = (terminal voltage V1*maximum discharge current I1) / battery discharge energy density W0.

[0241] 6. High temperature storage performance test

[0242] At 25°C, the secondary battery was charged to 4.5V at a constant current of 1C, then charged to a cutoff current of 0.05C at a constant voltage of 4.5V, left for 10 minutes, and then discharged to 2.5V at a constant current of 0.5C, and the discharge capacity D0 at this time was recorded. The secondary battery was placed in an environment of 60°C for 60 days. After that, the secondary battery was taken out and cooled to a battery surface temperature of 25°C. Subsequently, at 25°C, it was discharged to 2.5V at a constant current of 0.5C, then charged to 4.5V at a constant current of 1C, and then charged to a cutoff current of 0.05C at a constant voltage of 4.5V, left for 10 minutes, and discharged to a termination voltage of 2.5V at a constant current of 0.5C, and the discharge capacity D1 after high-temperature storage was obtained. High-temperature storage capacity retention rate (%) = (D1 / D0) × 100%.

[0243] 7. Test method for compacted density of membrane layer

[0244] The positive electrode sheet of the battery that meets the processability requirements is obtained, and a positive electrode sheet with a diameter of 14 mm is punched out using a punching machine. The mass m of the positive electrode sheet is measured using an electronic balance and a desktop digital thickness gauge. c , thickness d c ; Use a punching machine to punch out a sufficient number of aluminum foil substrates with a diameter of 14 mm, and use an electronic balance and a desktop digital thickness gauge to measure the mass m of the aluminum foil substrates respectively Al , thickness d Al .

[0245] Compacted density of positive electrode

[0246] Where: ρ is the compaction density of the positive electrode, in grams per cubic centimeter (g / cm 3 );m cis the mass of the positive electrode, in grams (g); m Al is the mass of the aluminum foil substrate, in grams (g); is the diameter of the positive electrode, in millimeters (mm); d c is the thickness of the positive electrode sheet, in micrometers (μm); d Al is the thickness of the aluminum foil substrate, in micrometers (μm).

[0247] 8. Test method for average particle size of primary particles

[0248] The particle morphology and size of the sample to be tested are obtained by SEM, and the software "LIBMAS Lithium-ion Battery Material Microscopic Intelligent Analysis System" is used to automatically identify the primary particles by AI, draw the particle outline, and obtain the particle quantity, number, area, and maximum caliper diameter. Take 2000 particles and calculate the average. The average particle size of the primary particles = the sum of all measured particle sizes (longest diameter) / the sum of all measured particle numbers.

[0249] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A lithium ion secondary battery, characterized in that: It comprises a positive electrode plate and an electrolyte, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode film layer arranged on at least one side of the positive electrode current collector; The positive electrode film layer includes a positive electrode active material, and the positive electrode active material includes a first positive electrode active material and a second positive electrode active material, wherein the first positive electrode active material includes a lithium-containing transition metal oxide, and the second positive electrode active material includes a lithium-containing transition metal phosphate; The electrolyte includes a solvent, an additive and a lithium salt, and the additive includes a cyclic sulfate ester compound.

2. The lithium ion secondary battery according to claim 1, characterized in that: The charging cut-off voltage v of the lithium-ion secondary battery satisfies: 4.3 V≤v≤5 V.

3. The lithium ion secondary battery according to claim 1 or 2, characterized in that: The cyclic sulfate ester compound comprises at least one of the compounds of formula (I) or modified compounds thereof: Among them, R1-R4 include at least one of halogenated or unhalogenated H, alkyl with 1-6 carbon atoms, alkenyl with 2-6 carbon atoms, alkoxy with 1-6 carbon atoms, acyloxy with 1-6 carbon atoms, ester with 2-6 carbon atoms, and cyclic sulfate with 4-7 membered rings.

4. The lithium ion secondary battery according to claim 3, characterized in that: R1-R4 also includes at least one of the groups of formula (II-I) to formula (II-IV): in, Indicates the bonding position, R5 includes at least one of halogen, alkyl having 1-6 carbon atoms, haloalkyl having 1-6 carbon atoms, and alkoxy having 1-6 carbon atoms, and the groups of formula (II-III) to (II-IV) are bonded to R1 and R3, or to R2 and R4.

5. The lithium ion secondary battery according to claim 3 or 4, characterized in that: The cyclic sulfate ester compound has a polycyclic structure.

6. The lithium ion secondary battery according to any one of claims 3 to 5, characterized in that: The cyclic sulfate ester compound includes at least one of the compounds having molecular formula (II) to (I-XII):

7. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: Based on the total mass of the electrolyte, the mass fraction m1 of the cyclic sulfate ester compound satisfies: 0.1%≤m1≤5%.

8. The lithium ion secondary battery according to claim 7, characterized in that: 0.5%≤m1≤2%。 9. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The ionic conductivity σ of the electrolyte satisfies: 7.5 mS / cm≤σ≤15 mS / cm.

10. The lithium ion secondary battery according to any one of claims 1 to 9, characterized in that: The lithium salt includes: at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, lithium bisoxalate borate, lithium difluorooxalate borate or lithium tetrafluorooxalate phosphate; optionally, the lithium salt includes lithium hexafluorophosphate.

11. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The concentration c of the lithium salt in the electrolyte satisfies: 0.9M≤c≤1.2M.

12. The lithium ion secondary battery according to any one of claims 1 to 11, characterized in that: The solvent includes at least one of a carbonate solvent and a carboxylate solvent.

13. The lithium ion secondary battery according to claim 12, characterized in that: The carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate and diethyl carbonate.

14. The lithium ion secondary battery according to claim 12, characterized in that: The carboxylate solvent includes at least one of methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl acrylate and ethyl acrylate.

15. The lithium ion secondary battery according to any one of claims 12 to 14, characterized in that: The carbonate solvent includes ethylene carbonate. Based on the total mass of the electrolyte, the mass fraction m2 of the ethylene carbonate satisfies: 10%≤m2≤30%.

16. The lithium ion secondary battery according to any one of claims 1 to 15, characterized in that: The additive includes fluoroethylene carbonate.

17. The lithium ion secondary battery according to any one of claims 1 to 16, characterized in that: In a cross section of the positive electrode film layer along the thickness direction of the positive electrode sheet, primary particles of the first positive electrode active material surround at least a portion of agglomerates of primary particles of the second positive electrode active material.

18. The lithium ion secondary battery according to any one of claims 1 to 17, characterized in that: The BET1 of the positive electrode active material satisfies: 0.5m 2 / g≤BET1≤4.5m 2 / g.

19. The lithium ion secondary battery according to any one of claims 1 to 18, characterized in that: The volume distribution particle size Dv50 of the positive electrode active material satisfies: 3.2 μm≤Dv50≤6 μm.

20. The lithium ion secondary battery according to any one of claims 1 to 19, characterized in that: The average particle size D1 of the primary particles of the first positive electrode active material satisfies: 1.6 μm≤D1≤2.6 μm; and / or The average particle size D2 of the primary particles of the second positive electrode active material satisfies: 40 nm ≤ D2 ≤ 250 nm.

21. The lithium ion secondary battery according to any one of claims 1 to 20, characterized in that: The lithium-containing transition metal oxide includes a molecular formula of Li n1 (Ni x1 Co y1 Mn z1 ) 1-n G n O 2-m K r or at least one of the compounds or modified compounds thereof, wherein G includes one or more of Zr, Al, Nb, Sr, B, Ba, Mg, Sn, Y, Na, Si, W and Ti, K includes one or more of P, F, N, S, F, Cl and I, 0.6≤n1≤1.5, 0.3≤x1≤0.7, 0.02≤y1≤0.15, x1+y1+z1=1, 0<n≤0.1, 0<m≤0.1, 0<r≤0.

1.

22. The lithium ion secondary battery according to claim 21, characterized in that: The average mass concentration ratio of K element in the outer region corresponding to 1 / 6 radius extending from the surface of the primary particle of the lithium transition metal oxide to the center is greater than the average mass concentration ratio of K element in the core region corresponding to 1 / 6 radius extending from the center of the primary particle to the surface.

23. The lithium ion secondary battery according to claim 21, characterized in that: The average mass concentration ratio a of the K element in the outer region extending from the surface of the primary particle of the lithium-containing transition metal oxide to the center corresponding to 1 / 6 of the radius satisfies: 0.1%≤a≤0.5%.

24. The lithium ion secondary battery according to claim 21, characterized in that: The average mass concentration ratio b of the K element in the core region extending from the center of the primary particle of the lithium-containing transition metal oxide to the surface corresponding to 1 / 6 of the radius satisfies: 0.01%≤b≤0.05%.

25. The lithium ion secondary battery according to any one of claims 1 to 24, characterized in that: The lithium-containing transition metal phosphate includes a molecular formula of Li n2 Fe x2 Mn y2 P z2 O j Q q or at least one of a compound or a modified compound thereof, wherein Q includes at least one of Al, Na, K, Mg, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.6≤n2≤1.15, 0<x2, 0≤y2, 0.9≤x2+y2≤1, 0.95≤z2≤1, 3.5≤j≤4, and 0≤q≤0.

1.

26. The lithium ion secondary battery according to any one of claims 1 to 25, characterized in that: Based on the total mass of the positive electrode active material, the mass fraction m3 of the lithium-containing transition metal phosphate satisfies: 5%≤m3≤40%.

27. The lithium ion secondary battery according to claim 26, characterized in that: In the case where the lithium-containing transition metal phosphate includes lithium iron phosphate, 5%≤m3≤15%; or In the case where the lithium-containing transition metal phosphate includes lithium iron manganese phosphate, 10%≤m3≤40%.

28. The lithium ion secondary battery according to any one of claims 1 to 27, characterized in that: The specific surface area BET2 of the positive electrode sheet satisfies: 2m 2 / g≤BET2≤5m 2 / g.

29. The lithium ion secondary battery according to any one of claims 1 to 28, characterized in that: The positive electrode plate has a plate porosity p measured by a true density method that satisfies: 22%≤p≤28%.

30. The lithium ion secondary battery according to any one of claims 1 to 29, characterized in that: The compaction density ρ of the positive electrode sheet satisfies: 3.0 g / cm 3 ≤ρ≤3.5g / cm 3 .

31. An electrical device, characterized in that: The electrical device comprises the lithium ion secondary battery according to any one of claims 1 to 30.

32. A method for charging a lithium-ion secondary battery, characterized in that: The charging method comprises: Charging the lithium-ion secondary battery at a preset rate Cset to a cut-off voltage v; Charging the lithium-ion secondary battery at the cut-off voltage v to a cut-off current i; Among them, 4.3V≤v≤5V, 0.02C≤i≤0.1C.

Citation Information

Patent Citations

  • Cathode Active Material With Silicon Carbide Additive

    CN112909225A

  • Lithium ion battery, preparation method thereof and electric automobile comprising lithium ion battery

    CN113130997A

  • Lithium ion battery

    CN113571774A

  • Lithium ion battery

    CN114122492A

  • Secondary battery and preparation method thereof, and battery module, battery pack and device comprising secondary battery

    CN114982002A

Cited By

  • Battery, battery pack, electric equipment and quality control method

    CN121546121A

  • Battery monomer, battery device, power utilization device and energy storage device

    CN122314859A

  • Battery monomer, battery device, power utilization device and energy storage device

    CN122337993A

  • Lithium-ion secondary battery and charging method thereof, and electric device

    WO2026145846A1